Edukasi Pencegahan Bullying Terhadap Anak Sekolah Dasar Pelag di Wilayah Desa Nagrak: Pengabdian - Abdul Gafur Josan; Andi Nadia Zata Amani; Arkaan Zachary Hermawan; Asyifa Nuramalia; Fahrul Assalam; Rafli Fathur Rahman; Rahmah Syahidah; Shera Lusiana Putri; Shofura Naila Syahidatulhaq; Sri Yulandasari Lajai Mandam; Muhamad Iqbal Rhamadianto (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Bullying is a serious issue in the educational environment that significantly affects children’s psychological and social development. This problem is still prevalent at the elementary school level, including at SDN Pelag in Nagrak Village, which highlights the need for preventive measures through education. This community service activity aimed to improve students’ understanding of bullying, covering its definition, types, impacts, and prevention strategies. The method employed was a quasi-experimental approach using a pre-test and post-test design, combined with participatory education through interactive discussions, Q&A sessions, self-reflection, and psychoeducation. The program involved 87 students from grades III to VI. The analysis results indicated a significant increase in students’ knowledge, shown by an improvement from 77% in the pre-test to 91% in the post-test. These findings demonstrate that participatory education effectively fosters awareness among students to reject bullying and helps create a safe and comfortable school environment. This program is expected to serve as a sustainable bullying prevention model through collaboration among schools, teachers, and parents.